ANALYSIS OF THE GLOBAL DYNAMICS OF ROAD USER INJURIES RESULTING FROM ROAD ACCIDENTS - Тарасенко, Олександр; Фукалова, Олена; Обертінська, Віолетта (SWorldJournal, 2026)
The work examines the dynamics of injuries resulting from traffic accidents in the world in relation to types of road users and regions over the past 20 years.